PENAMBAHAN ASAM AMINO LISIN PADA PAKAN BUATAN TERHADAP KELANGSUNGAN HIDUP DAN PERTUMBUHAN IKAN KAPIAT (Barbonymus schwanenfeldii) - Balqis, Az-zahra; Isriansyah, Isriansyah; Maidie, Asfie (JARI : Jurnal Akuakultur Rawa Indonesia, 2025)
The objectives of this experiment were to analyze the effect of the supplementation of amino acid lysine in artificial feed on the survival rate and growth of tinfoil barb (B. schwanenfeldii) and to determine the differences dose of amino acid lysine supplementation in artificial feed that can increase of the survival rate and growth of tinfoil barb (B. schwanenfeldii). The method used in the research were experimental method by adding lysine to artificial feed with different doses, namely P1 (0%), P2 (3%), P3 (6%), P4 (9%) per weight of feed. Feeding to fish were done ad satiation every day. The experimental design used in this study was a complete randomized design consisting of four treatments and three replicates. The results showed that the addition of lysine to artificial feed had no significant effect on survival rate, total length growth (P>0.05) but absolute weight growth and daily growth rate gave a significantly different effect (P<0.05). The observation results during the study showed the highest values total length growth P3 (6%) 3.00 cm, absolute weight growth P3 (6%) 18.75 g, and daily growth rate P3 (6%) 0.31 g/day.